Optimizing the Treatment Pattern for De Novo Metastatic Nasopharyngeal Carcinoma Patients: A Large-Scale Retrospective Cohort Study - Sun, Xue-Song; Liang, Yu-Jing; Chen, Qiu-Yan; Guo, Shan-Shan; Liu, Li-Ting; Sun, Rui; Luo, Dong-Hua; Tang, Lin-Quan; Mai, Hai-Qiang (Frontiers in Oncology, 2020)
Objectives: To investigate the optimal treatment pattern in patients with de novo metastatic nasopharyngeal carcinoma (NPC). Methods: We assessed 502 consecutive and unselected de novo metastatic NPC patients in Sun Yat-sen University Cancer Center (SYSUCC) from November 2006 to October 2016 in our study. All patients were treated with palliative chemotherapy (PCT) and 308 patients received locoregional radiotherapy (LRRT) subsequently. Our primary study endpoint was overall survival (OS). Results: The patients treated with LRRT were associated with improved survival on univariate analysis (3-year OS rate 63.7% vs. 31.8%, P < 0.001) and multivariate analysis (HR 0.52, 95%CI 0.40–0.68, P < 0.001). The overall survival benefit of more than 4 PCT cycles was significant in female (HR 0.45, 95% CI 0.24-0.86, P = 0.016) and patients with multiple metastatic sites (HR 0.42, 95% CI 0.26-0.66, P < 0.001). The application of concurrent chemotherapy (CCT) was not associated with better survival among patients receiving LRRT (HR 1.31, 95% CI 0.92-1.86, P = 0.141). Conclusion: LRRT prolonged survival in de novo metastatic NPC. For patients treated with multiple metastatic sites, more than 4 cycles of PCT is necessary. CCT does not improve survival in de novo metastatic NPC patients.